Predicting the Power of Famous Sport Endorser Indices on the Tendency to Purchase Sporting and Non-porting Goods: A Quasi-experimental Study - Amir Hossein Sepehrian; Seyed Morteza Azimzadeh; Mohammad Keshtidar (Allameh Tabataba'i University Press, 2020)
Purpose: Nowadays, the use of sports and famous athletes in advertising has become one of the most common advertising practices. Therefore, the purpose of this research was to investigate the ability of predicting the indices of attractiveness, expertise, and trustworthiness of the renowned sport endorser on the consumers' willingness to buy sporting and non-sporting goods. Method: This study was a quasi-experimental study on a sample of 150 students of sport science at Ferdowsi University of Iran. The statistical sample was divided into two homogeneous groups; for one month, one group watched the advertisements of an artificial sport product and the other group watched the advertisements of an artificial non-sport product endorsed by the famous sport personality on the telegram. Finally, the results were analyzed by completing standard questionnaires of purchase willingness (Zichkowski, 1985) and advertising celebrities (Ohanian, 1990) and simultaneous regression statistical methods. Results: The results showed that all three indices of attractiveness, expertise, and trustworthiness of the renowned sports endorser have high predictive power for the tendency to purchase sporting and non-sporting goods. Also in the sporting goods group, the expertise, and in the non-sporting goods group, the attractiveness had the highest predictive power of tendency to buy. On the other hand, there is a significant difference between the perception of the popular sport endorsing indices in advertising sporting and non-sporting goods. Conclusions: Through a promotional period for two endorsed sporting and non-sporting products, this study provides useful findings for product and service institutions to select and employ renowned athletes to endorse their products and influence consumers' purchase intention. In the text, the detailed descriptions of the expected results and discussions have been reported.